PELATIHAN PEMASARAN DIGITAL UMKM ROTI AURY, DAN KEGIATAN BERSIH-BERSIH MAKAM DALAM RANGKA SADRANAN MAKAM SHUUFI - Ananta, Tesa; Khoiriyah, Kholidatul; Dheba Ammilia Araffat, Aurell; Muhamad Fadkhurohim, Bilard; Stevani Rama Repi, Gabriela; Pramesti Nur Cahyani, Hardinar; Nur, Inayah Islami; Iskanabila, Syifa Zahra; Ramadhanty, Thifa Rizma; Nugroho, Verdiansyah Adi; Barkhowa, Mokhammad Khukaim (Unperba Press, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy. However, challenges in digital marketing are still an obstacle for MSME actors. This community service activity aims to improve MSME digital marketing strategies through training in the use of the Canva and CapCut applications, at Roti Aury in Tegalrejo, Salatiga City, while MSMEs also support the preservation of local culture. The methods used are training and grave cleaning activities. The results of the study showed that before the training, digital marketing at Roti Aury was still less than optimal. After the training, there was an increase in the use of social media for product promotion, the creation of more attractive visual content, and a better understanding of digital marketing. In addition, involvement in Sadranan cultural activities helps strengthen the relationship between MSMEs and the local community. Sadranan is a cultural tradition that is carried out as a form of gratitude and as a prayer for the safety and blessings of the local community. In addition, Sadranan is an event to strengthen social relations and preserve local culture that has been passed down from generation to generation.